The Importance of Ecological and Spiritual Approaches in Chemical Engineering towards Practical Conception of Sustainable Development - Azizan, Ramli; Mohd Shaiful Zaidi, Mat Desa (2011)

(untitled)
The issues in sustainable development are of two kinds; the interdependent of three principle pillars of sustainable development-environment, social, and economy development and human spiritual development. The main objective of this paper is to discuss on the importance of spiritual enhancement and ecological approach in chemical engineering to develop a notion of conception for sustainability. We elaborate and discuss contemporary Islamic principle named “Jurisprudence of Priorities” ( Fiqh Al-Aulawiyyat) and what it suggests for sustainability and concurrently delineate the need for ecological approach in chemical engineering. The study was conducted based on available published articles from books, handbooks, journals, and other online reliable sources related to environment and sustainability. The study concentrates on both Islamic jurisprudence principle in conserving the nature and ecological approach in chemical engineering. The examples presented in this article provide new information on the importance of spiritual development and ecological considerate in chemical engineering towards successful sustainable development. This study is perhaps one of the first to address the incorporation of spiritual enhancement (Islamic principle) and ecological approach in chemical engineering to create environmental awareness among world community.